INCLUSIVE PEDAGOGY: ADAPTING TO DIVERSE LEARNING NEEDS IN MILITARY TRAINING - Dadaboyeva Fayyoza Khikmatulloyevna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the integration of inclusive pedagogy in military training, emphasizing the importance of accommodating diverse learning needs. It examines theoretical frameworks, challenges, strategies, and case studies to highlight the benefits of inclusive education in fostering well-rounded leaders in military academies.